Ab initio prediction of a new allotrope of two‐dimensional silicon. Issue 3 (25th January 2017) - Tang, Jiang; Li, Jin; He, Chaoyu; Zhang, Chunxiao; Ouyang, Tao; Tang, Chao; Xiao, Huaping; Zhong, Jianxin
Abstract : Silicene, a promising candidate for future electronic devices, has been fabricated only on supporting substrates as silicon atom prefers to form the sp 3 hybridization structure. Therefore, it's important to search more stable two‐dimensional (2D) silicon allotropes and several 2D silicon allotropes have been proposed recently. In this work, we predict a new type of 2D silicon allotrope (called OTDS) based on ab initio structure, phonon‐mode and molecular dynamics calculations. OTDS has the in‐plane octagonal tiling (OT) pattern with dumbbell‐like structures and silicon atoms in OTDS are four‐ and three‐coordinated. OTDS is a semiconductor with a large band gap (about 1.5 eV by HSE calculation) and the band gap can be tuned effectively by the in‐plane strain.Perspective and side views of the atomic structure of OTDS. Abstract : A new type of 2D silicon allotrope (called OTDS) is proposed by the ab initio structure, phonon‐mode and molecular dynamics calculations. In their results the authors demonstrate that OTDS possesses relatively good stability. OTDS is a semiconductor with a large band gap, which is quite different from the zero‐gap of silicene. The new structure of OTDS can be an important contribution for further 2D silicon materials.